Global mergers and acquisitions. - Soofi, Abdol S.; Zhang, Yuqin (Finance and financial management collection., 2018)
This book primarily deals with corporate restructuring through mergers and acquisitions (M & As). It critically examines all functions that must be performed in completing an M & A transaction. Accordingly, the book gives a bird's-eye view of processes of M & A. Domestic and cross-border M & As are very similar in many respects even though differences between them also exist. This book discusses the cross-border financial issues such as international finance and multinational financial management, which also arise in cross-border M & A transactions.